Analysis of factors influencing the job satisfaction of medical staff in tertiary public hospitals, China: A cross-sectional study - Shi, Xiang; Xiong, Dekai; Zhang, Xingmin; Han, Miaomiao; Liu, Liu; Wang, Jinian (Frontiers in Psychology, 2023)
Introduction Since the outbreak of the novel coronavirus pneumonia (COVID-19), China has entered normalization phase of its epidemic prevention and control measures that emphasizes ‘precise prevention and control,’ ‘dynamic zeroing’, and ‘universal vaccination’. However, medical staff continue to face physical and mental stress. The present study aimed to investigate the job satisfaction of medical staff in China, as well as any associated factors. Methods 2,258 medical staff completed a questionnaire specially designed for this study. Independent samples t-tests, one-way analysis of variance, and binary logistic regression were used to analyze associated factors. Results Overall, 48.4% of the participants expressed satisfaction with their job; the highest-scoring dimension was interpersonal relationships (3.83 ± 0.73), while the lowest scoring dimension was salary and benefits (3.13 ± 0.94). The logistic regression model indicated that job satisfaction among medical staff is associated with being aged 40–49 years [odds ratio (OR) = 2.416] or > 50 years (OR = 2.440), having an above-undergraduate education level (OR = 1.857), holding a position other than doctor [i.e., nurse (OR = 3.696) or ‘other’ (OR = 2.423)], having a higher income (OR = 1.369), and having fewer monthly overtime shifts (OR = 0.735–0.543). Less than half of the medical staff expressed satisfaction with their job, indicating that the overall level is not high. Discussion This research enriches the study of medical workers’ job satisfaction during periods when epidemic prevention and control has become familiar and routine. To improve medical workers’ job satisfaction, administrators should seek to enhance medical staff’s remuneration, reduce their work pressure, and meet their needs (where reasonable).